Improvement of economic consistency level is the main way of revival - Pshinko, A. N.; Myamlin, V. V.; Myamlin, S. V. (Science and Transport Progress, 2011)
The necessity of using a systematic approach in constructing a working model of the economy is shown. The need to improve the system level of the economy is discussed. The main reason, «the financial and economic» crisis, which disturbs the balance between the supply of goods and effective demand for them is called the category of «profit». Reference is made to the Institute developed a “model of high performance of the national economy”, which will eliminate all negative phenomena inherent in the modem model of economic activity and GDP increase several times.